Mentoring as an effective method of professional development and personnel training - Rekun, Ganna; Baboshko, Anna; Bushlya, Darya; Рекун, Аннa; Бабошко, Анна; Бушля, Дарья (Харківський національний автомобільно-дорожній університет, 2015)
Nowadays mentoring is a very important part of personnel adaptation in a company. It helps to provide the enterprise with qualified and well-trained staff and to share the experience and corporative culture of the enterprise. In future the use of mentoring will bring significant results such as high level of competitiveness, solid team spirit, implementation of innovations and a new look at different complicated tasks. The article is devoted to study mentoring processes in a company. The main objective of the article is to research the concept of mentoring, to suggest different structures of mentoring and the features of this process in the company. It was proposed to consider the necessity to integrate all the elements into a united system of mentoring and to structure approaches to this instrument, depending on the scale and sphere of the enterprise. It was suggested to classify them into three main categories: formal, informal and mixed. Despite the differences in the various structures of the mentoring process the implementation is always accompanied by social-emotional, professional and personal development of staff. Due to the multi-stage nature of mentoring implementation most of the companies experience difficulties that can be avoided by providing a detailed analysis of business processes and informing staff about all aspects of a mentoring program.
Менторинг как эффективный метод профессионального развития и обучения персонала
Keywords: mentoring; mentor; mentee; professional development; adaptation; personnel; staff; менторинг; наставник; ментор; профессиональное развитие; адаптация; персонал; штат; 331.108.45